CLAIMS OF SCIENTIFIC APPROACH IN AN ENGLISH LESSON TRANSCRIPT - Munir, Ahmad (Paramasastra, 2015)
As  the  generic  approach  for  teaching  all  subjects  in  the  2013 Curriculum,  five stages  of  Scientific  approach  (SA)  are  subject  to  adaptation  (Permendiknas 103/2014).  In  response  to  this, English  lessons have married  it with genre-based approach  (GBA)  through  stages  of  instruction,  namely  building  context  or knowledge of the field, modeling of text and deconstructing  it,  joint construction of  text, and  independent  instruction of  text. This paper  reports an analysis of an English  lesson  transcript which has been claimed as applying scientific approach in  Hafidah?s  (2014)  study.  Through  a  qualitative  analysis,  all  the  classroom language  used  by  both  teacher  and  her  students  were  categorized  in  to  their intended  five SA  stages, GBA  stages and  their pedagogical  intentions  (Johnson, 1990).  The whole  classroom  language  use  was  then  analysed  for  its  inductive-deductive  reasoning.  Results  show  that  there  is  little  evidence  of  scientific approach in that lesson transcript.